2000
DOI: 10.1097/00004424-200011000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Effect of Iodinated High-Viscosity Contrast Medium in the Rat Kidney

Abstract: This preliminary experience in rats shows that dynamic diffusion-weighted MRI can be used to study noninvasively the in vivo renal hemodynamic response after injection of iodinated contrast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
3
19
0
5
Order By: Relevance
“…Our results are partially supported by a previous report by Laissy et al (19). In their study, a dynamic serial DW-MRI was performed to monitor the effects of isosmotic iodixanol on the renal function based on a rat model.…”
Section: Discussionsupporting
confidence: 89%
“…Our results are partially supported by a previous report by Laissy et al (19). In their study, a dynamic serial DW-MRI was performed to monitor the effects of isosmotic iodixanol on the renal function based on a rat model.…”
Section: Discussionsupporting
confidence: 89%
“…However, our data provide values which are in the mid-range of those reported to date, and the lower standard deviations of our results provide further confidence in our findings. Some authors [8,13,16] have reported higher values in the medulla as compared with the renal cortex, and this finding was validated by the results obtained by Laissy et al in rats [14]. We did not try to evaluate ADC values in the cortex and in the medulla separately because it may be difficult and inaccurate to position the ROI cursor on the renal cortex and medulla of the kidney separately, as already pointed out by Fukuda et al [9].…”
Section: Discussionsupporting
confidence: 73%
“…The kidney is well suited for diffusion studies because of its high blood flow and its fluid transport function. According to some authors [13,14], these factors can explain the higher renal ADC values as compared with other organs.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, only a few studies have involved measurement of water diffusion in the kidneys [11][12][13][14][15]. Some investigators have reported higher values in the medulla than in the cortex of the kidney [11,15], whereas others have reported the opposite [13,14].…”
Section: Discussionmentioning
confidence: 99%